PERANAN DESAIN KEMASAN DALAM DUNIA PEMASARAN - Suharto Cenadi, Christine (Institute of Research and Community Outreach - Petra Christian University, 2000)
Packaging becomes a striker because its function directly encounters with customers. Hence%2C packaging must be able to give spontaneous impression to influence customer s positive actions in the market. In the cruel competition situation%2C aesthetics becomes an additional point that also functions as a powerful